The role of thoracoscopic biopsies in the diagnosis of pleural tuberculosis. (2019) - Haralsingh, A.; Rawlins, R.
Abstract: Tuberculosis (TB) is a significant public health problem in many developing countries. In many cases, tuberculosis may present a significant diagnostic challenge. A 32-year-old male Chinese immigrant presented to our institution with a fever and non-productive cough. He was found to have a right pleural effusion, for which a chest drain was inserted. His tuberculin skin test was unreactive (0mm) although he was not immunocompromised (HIV negative). All cultures were negative, and 3 sputum samples and his pleural fluid sample tested negative for acid-fast bacilli. A computed tomography (CT) scan of his chest revealed features suggestive of an early empyema. There was no evidence suggestive of a malignant effusion. In an effort to attain a diagnosis, he underwent a video-assisted thoracoscopy (VATS) procedure with pleural drainage and biopsies. Anti-tuberculosis therapy (ATT) was commenced due to a high level of suspicion after failure of empirical therapy. Although the Ziehl-Neelsen stain for acid fast bacilli was negative, pleural biopsies demonstrated active chronic granulomatous pleuritis with many Langerhans type giant cells highly suggestive of tuberculosis. He was responsive to treatment and completed 6 months of ATT with complete clinical resolution. In young, immunocompetent patients with an exudative, culture-negative effusion, the diagnosis of pleural tuberculosis must be considered. Pleural biopsy is the gold standard for diagnosing pleural TB but demonstration of acid-fast bacilli or necrotizing granulomas in the specimen are not absolutely necessary to make the diagnosis.